Genome-wide long non-coding RNA expression profile and its regulatory role in the ileocecal valve from Mycobacterium avium subsp. paratuberculosis-infected cattle - Badia-Bringué, Gerard; Asselstine, Victoria; Cánovas, Ángela; Alonso-Hearn, Marta (Frontiers in Veterinary Science, 2025)
Bovine paratuberculosis (PTB) is a chronic enteritis caused by Mycobacterium avium subsp. paratuberculosis (MAP), which results in significant economic losses to the dairy industry worldwide. Long non-coding RNAs (lncRNAs) play a crucial role in regulating the host immune response due to their interaction with transcripts in proximity. However, their annotation in cattle remains limited, and their role in cattle naturally infected with MAP has not been fully explored. In this study, lncRNAs were identified in the transcriptome of ileocecal valve samples from control cows without lesions (N = 4) and with PTB-associated focal (N = 5) and diffuse (N = 5) lesions in intestinal tissues using RNA sequencing. The raw reads were uploaded into the CLC Bio Genomics Workbench, and the trimmed reads were mapped to the Bos taurus ARS_UCD1.2.109 reference genome using the Large Gap Read Mapping tool. The resulting annotation allowed the identification of 1,434 LncRNAs, 899 of which were novel, using the FlExible Extraction of LncRNA pipeline. LncRNA differential expression (DE) analysis performed with DESeq2 allowed the identification of 1, 6, and 2 DE lncRNAs in the comparisons of cows with focal lesions versus (vs) controls, diffuse lesions vs. controls, and diffuse vs. focal lesions, respectively. Best lncRNA partner analysis identified expression correlations between the lncRNA1086.1, lncRNA ENSBTAG00000050406, and lncRNA_2340.1, and the Inactive Phosphatidylinositol 3-Phosphatase 9 (MTMR9), GM Domain Family member B (RGMB), and the homeobox A6 (HOXA6), respectively. The MTMR9 negatively regulates apoptosis, the RGMB positively regulates IL-6 expression, and the HOXA6 regulates cell differentiation and inflammation. The results of the quantitative trait locus (QTL) enrichment analysis showed that the DE lncRNAs were located in genomic regions previously associated with clinical mastitis, HDL cholesterol, bovine tuberculosis, paratuberculosis, and bovine leukosis susceptibility. The identified DE lncRNAs could allow the development of novel PTB diagnostic tools and have potential applications in breeding strategies for PTB-resistant cattle.